Regulatory pathways for vaccines for developing countries - Milstien Julie; Belgharbi Lahouari (The World Health Organization, 2004)
Vaccines that are designed for use only in developing countries face regulatory hurdles that may restrict their use. There are two primary reasons for this: most regulatory authorities are set up to address regulation of products for use only within their jurisdictions and regulatory authorities in developing countries traditionally have been considered weak. Some options for regulatory pathways for such products have been identified: licensing in the country of manufacture, file review by the European Medicines Evaluation Agency on behalf of WHO, export to a country with a competent national regulatory authority (NRA) that could handle all regulatory functions for the developing country market, shared manufacturing and licensing in a developing country with competent manufacturing and regulatory capacity, and use of a contracted independent entity for global regulatory approval. These options have been evaluated on the basis of five criteria: assurance of all regulatory functions for the life of the product, appropriateness of epidemiological assessment, applicability to products no longer used in the domestic market of the manufacturing country, reduction of regulatory risk for the manufacturer, and existing rules and regulations for implementation. No one option satisfies all criteria. For all options, national infrastructures (including the underlying regulatory legislative framework, particularly to formulate and implement local evidence-based vaccine policy) must be developed. WHO has led work to develop this capacity with some success. The paper outlines additional areas of action required by the international community to assure development and use of vaccines needed for the developing world.